Assessment of the availability and reason for non-utilization of reproductive and child health services at urban primary health centers Lucknow - Kumar, Santosh; Agarwal, Monika; Mishra, Prabhaker (International Journal Of Community Medicine And Public Health, 2023)
Background: Urban Primary Health Centres (UPHC)are different from conventional rural PHCs in term of size, functions, focus on ambulatory care, limited staff and infrastructure. UPHC is also expected to deliver certain job-functions of Subcentre through its outreach services. In view of these considerations, it is, therefore, appropriate that a separate list of standards is developed. Methods: This was a cross-sectional study conducted on 320 Recently delivered women (up to 24 months) and children less than 24 months of age residing in catchment areas of urban PHCs and 8 urban primary health centers of Lucknow district, using multistage sampling technique. Results: The infrastructural availability at urban PHCs showed that clean drinking water for patients was available at only 75 % of U-PHCs. Unfortunately, only 50 % of the labs were functional. Additionally, essential tests for ANC were available at only 50 % of U-PHCs. Majority (48.7%) of RDW were not aware of U-PHCs nearby. Most (26.7%) common reason cited for non-utilization of U-PHCs was the availability of better hospital/ bigger hospitals nearby. According to 8.7 %, doctors/staff are not available all time at U-PHCs. About 12.8 % of RDW also reported that the delivery facility was not available. According to 18.0 % RDW, several other reasons were unavailability of drugs, inadequate cleanness, distance, staff behaviour, etc. Conclusions: Only four (50%) labs were functional at UPHC. The main reason of non-utilization of urban primary health centers not aware about location of U-PHC nearby and bigger hospitals nearby, investigations not available, several other reasons were unavailability of drugs, inadequate cleanness, distance, staff behaviour,